Net-structure polymer cement grinding aid and preparation method thereof

By using a mesh structure polymer cement aid, the composite mesh structure of borax-alcoholamine polymer, glycol compound and nanosilicon dioxide is solved by using the composite mesh structure of borax-alcoholamine polymer, glycol compound and nanosilicon dioxide, the stability of the material layer and cement strength in the vertical grinding mill are improved. The problem has achieved a significant improvement in high-efficiency grinding and cement strength.

CN119430724APending Publication Date: 2025-02-14HUAXIN CEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661029.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing vertical grinding cement aids have limited effects in improving the stability of the material layer and cement strength, and it is difficult to meet the needs of efficient grinding and cement strength improvement during the vertical grinding process.

Method used

A web-like structure polymer cement aid is used, which consists of borax-alcoholamine polymer, glycol compounds, nanosilicon dioxide and water. It forms a composite web-like structure through cross-linking reaction, covering the surface of the material layer. , maintain the stability of the material layer and increase the strength during the cement hydration process.

Benefits of technology

The vertical grinding efficiency is significantly improved, the stability of the cement material layer is enhanced, and the strength of the cement is significantly improved during the cement hydration process, solving the problem of limited effect of traditional agitators in vertical grinding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a network-structure polymer cement grinding aid and a preparation method thereof. The cement grinding aid is prepared from a borax-alcohol amine polymer, a glycol compound, nano silicon dioxide and water, the borax-alcohol amine polymer is obtained by crosslinking an alcohol amine compound, borax and water under an alkaline condition, and the viscosity of the borax-alcohol amine polymer is 1500-2000 mPa.S; the molar ratio of the alcohol amine compound to the borax to the glycol compound to the nano silicon dioxide is (2-4): 1: (1-2): (0.5-1). The cement grinding aid has good material layer stability in the grinding process of the vertical mill, the grinding efficiency of the vertical mill is improved, the cement strength can be improved in the cement hydration process, and the preparation method is simple and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement admixtures, and in particular to a network structure polymer cement grinding aid and a preparation method thereof. Background Art

[0002] Cement grinding process can be divided into two types: vertical mill and tube mill (ball mill). Compared with tube mill, vertical mill has significant advantages. Without steel balls and steel segments, vertical mill naturally avoids metal collision and wear. The metal wear is small and the noise is low. In addition, its own powder selection function avoids over-grinding.

[0003] In the ball mill, the material is crushed by impact and friction, while in the vertical mill, the grinding force on the material is mainly extrusion, supplemented by grinding. When grinding cement with a vertical mill, the material is dry, the fineness of the cement grinding product is high, the material circulation volume is large, the circulating material is very fine, and the fluidity is good. Under the action of the centrifugal force of the millstone, it is quickly thrown out of the millstone and carried away by the high-speed airflow blown out by the wind ring, making it difficult to form a stable material layer.

[0004] In the vertical mill cement production process, the cement is required to have good material layer stability during the time the grinding disc stays, which is convenient for the grinding roller to work. In order to stabilize the material layer, water needs to be sprayed on the surface of the material layer, but it will affect the quality of the cement. Cement grinding aid is a chemical additive used to improve the effect and performance of cement grinding. It can significantly increase the cement output per unit hour, the strength of cement at various ages, and improve its fluidity. The main raw material of traditional cement grinding aids is small molecule substances such as alcoholamines, which can effectively solve the cement agglomeration problem in the process of producing cement in ball mills. However, its effect on stabilizing the material layer in vertical mill grinding is limited, and it cannot effectively improve the vertical mill output. Therefore, it is particularly important to develop cement grinding aids for vertical mill grinding.

[0005] At present, some cement grinding aids for vertical mills have been developed, but they generally have limited effects on stabilizing the material layer and improving the strength of cement. Therefore, it is urgent to develop a vertical mill cement grinding aid with material layer stabilization and strength improvement effects. Summary of the invention

[0006] In order to solve the problems existing in the background technology, the present invention provides a network structure polymer cement grinding aid and a preparation method thereof. The cement grinding aid has good material layer stabilization effect and improves the efficiency of the vertical mill during the vertical mill process, can improve the cement strength during the cement hydration process, and the preparation method is simple and efficient. The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, the present invention provides a network structure polymer cement grinding aid, which is composed of a borax-alcoholamine polymer, a glycol compound, nano-silicon dioxide and water. The borax-alcoholamine polymer is obtained by a cross-linking reaction of an alcoholamine compound, borax and water under alkaline conditions, and has a viscosity of 1500-2000 mPa·S. The molar ratio of the alcoholamine compound, borax, glycol compound and nano-silicon dioxide is (2-4):1:(1-2):(0.5-1).

[0007] Borax reacts with alcoholamine compounds to form a "network structure" of borax-alcoholamine polymers with borax as the central crosslinker and alcoholamine compounds as ligands. Borax has multiple hydroxyl groups in the borax-alcoholamine polymer network, and alcoholamine compounds have multiple strong hydroxyl structures with nitrogen atoms as the center, which can be effectively adsorbed on the surface of powder particles, so that the "network structure" of borax-alcoholamine polymers can be well covered on the material layer, maintaining the stability of the material layer during the grinding process and ensuring the grinding efficiency; Nano-silicon dioxide can play a "micro-aggregate" filling role in the early stage of cement hydration, making the slurry denser and improving the cement strength. At the same time, as During the hydration reaction, nano-silica reacts with the hydration product calcium hydroxide to produce volcanic ash, which increases the CSH gel content that is beneficial to strength and improves cement strength. The glycol compound has a multi-hydroxy structure, which gives the entire cement grinding aid a good grinding effect. At the same time, the hydroxyl group of the glycol compound plays a bridging role, further interweaving the borax-alcoholamine polymer with a "network structure" and nano-silica to form a composite network structure of nano-silica and borax-alcoholamine polymer. The intermediate oxygen of the glycol compound is adsorbed on the surface of the material, which increases the coverage of the composite network structure on the material layer, enhances the stability of the vertical abrasive layer, and improves the grinding efficiency.

[0008] During the cement hydration process, the composite network structure decomposes and releases system substances as the hydration reaction occurs. 4 O 7 2- It reacts with calcium ions in the slurry to form calcium borate, which wraps around the cement particles to form a semi-protective film, preventing the hydration products from being generated too quickly, making the cement structure denser; at the same time, as the hydration reaction proceeds, osmotic pressure is generated inside and outside the film, causing the calcium borate film to partially swell and crack, accelerating the reaction, thereby further improving the strength; the filling effect of nano-silicon dioxide and the volcanic ash reaction increase the favorable CSH gel content, improve the density of the cement structure, and thus enhance the strength of the cement. There is an unshared electron pair on the central N atom in the molecular structure of the alcoholamine compound, which promotes the alcoholamine compound to react with the metal ion Fe in the slurry. 3+ 、Al 3+Complexation occurs, increasing the solubility of metal ions in the slurry, accelerating the diffusion of metal ions in the slurry, accelerating the dissolution rate of intermediate minerals, continuously promoting the occurrence of cement hydration reaction, and improving cement strength. The components in the system work synergistically to further improve the strength while improving the grinding performance of cement.

[0009] According to the above scheme, the alcohol amine compound is one or more of N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, and N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide.

[0010] Compared with triethanolamine, diethanol monoisopropanolamine and other alcohol amines commonly used as grinding aids, the alcohol amine compound selected in the present invention has more molecular branches, is more conducive to generating a stable network structure, has more hydroxyl groups and nitrogen atoms under the same conditions, reduces the degree of sealing of hydration products, and can continuously promote cement hydration.

[0011] According to the above scheme, the mass concentration of borax-alcoholamine polymer obtained by cross-linking the olamine compound, borax and water is 60-70wt%, and the mass concentration of the network structure polymer cement grinding aid is 60-70wt%.

[0012] According to the above scheme, the glycol compound is one or more of tetraethylene glycol, pentaethylene glycol and hexaethylene glycol.

[0013] According to the above scheme, the purity of the nano silicon dioxide is greater than 99.5%, the hydroxyl content is greater than 40%, and the particle size is 10nm~30nm.

[0014] According to the above scheme, in the cement vertical mill grinding process, the amount of the network structure polymer cement grinding aid is 0.03-0.07wt% of the cement.

[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned network structure polymer cement grinding aid, comprising the following steps: S1. cross-linking an olamine compound, borax and water to obtain a borax-olamine polymer; S2. Add glycol compound, nano silicon dioxide and water to the borax-alcoholamine polymer obtained in step S1, and stir to obtain the network structure polymer cement grinding aid.

[0016] According to the above scheme, step S1 includes: S1.1 Mix the alcohol amine compound, borax and water to obtain a mixed solution, stir and heat it to 50-70°C, add alkaline regulating solution while stirring to adjust the pH of the system to 9.0-10, and carry out cross-linking reaction for 40-60 minutes; S1.2 adding an acidic regulating liquid to adjust the pH of the system to 6-7 to terminate the cross-linking reaction, thereby obtaining the borax-alcoholamine polymer.

[0017] During the cross-linking process of borax and olamine compounds, the alkaline regulator continuously promotes the forward progress of the cross-linking reaction to generate a network structure. The larger the molecular weight, the more serious the molecular entanglement, the greater the flow resistance, and the higher the viscosity. Excessive cross-linking reaction generates a network structure with a larger molecular weight. Although it has a better effect on the stability of the material layer during the grinding process, the coverage of the cement particle surface is too high, which is not conducive to the subsequent hydration reaction process. The addition of an acidic regulator regulates the degree of cross-linking reaction. By controlling the viscosity range, the molecular weight of the cross-linked product is controlled to generate the desired target network structure of borax-olamine polymers. The generated network structure of borax-olamine polymers can cover the material layer well, maintain the stability of the material layer during the grinding process, and ensure the grinding efficiency. At the same time, the generated network structure of borax-olamine polymers will not excessively cover the surface of cement particles, so that the cement particles can continue to hydrate and enhance strength.

[0018] According to the above scheme, the alkaline regulating liquid is one or more of sodium hydroxide, lithium hydroxide and potassium hydroxide solutions, with a concentration range of 0.5~1wt%, and the acidic regulating liquid is one or more of acetic acid, tartaric acid and maleic acid solutions, with a concentration range of 0.1~0.4wt%.

[0019] According to the above scheme, the stirring time in step S2 is 25 to 40 minutes.

[0020] The beneficial effects of the present invention are: 1) The network structure polymer cement grinding aid provided by the present invention is formed by cross-linking borax and alcohol amine to form a borax-alcohol amine polymer with a network structure, and further forming a stable composite network structure system with the borax-alcohol amine polymer, nano-silicon dioxide and glycol compound. It can well stabilize the material layer during the vertical mill grinding process, improve the grinding efficiency of cement particles, and has an excellent grinding aid effect; 2) The network structure polymer cement grinding aid provided by the present invention can form a denser structure during the cement hydration process, promote the continuous hydration of cement, and further improve the strength of cement; 3) The preparation method of the network structure polymer cement grinding aid provided by the present invention is simple, safe, environmentally friendly, and has good controllability. The raw materials are easily available, can be industrialized, and have significant practical application effects. DETAILED DESCRIPTION

[0021] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0022] It should be noted that in the description of the embodiments of the present application, the description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0023] In order to improve the stability of the material layer during the cement vertical mill process, improve the grinding efficiency, and at the same time improve the strength of cement, the inventors compounded the borax-alcoholamine polymer formed by cross-linking borax and alcoholamine compounds with nano-silicon dioxide and glycol compounds to obtain a cement grinding aid with a composite network structure system, which is used in the cement grinding vertical mill. The network structure polymer cement grinding aid can cover the material layer, improve the stability of the vertical mill material layer, thereby improving the vertical mill efficiency, and improve the cement strength during the cement hydration process.

[0024] The invention provides a network structure polymer cement grinding aid, which consists of a borax-alcoholamine polymer, a glycol compound, nano silicon dioxide and water. The borax-alcoholamine polymer is obtained by cross-linking the alcoholamine compound, borax and water under alkaline conditions, and has a viscosity of 1500-2000 mPa·S. The molar ratio of the alcoholamine compound, borax, glycol compound and nano silicon dioxide is (2-4):1:(1-2):(0.5-1).

[0025] In some specific embodiments, the alcoholamine compound is one or more of N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, and N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide.

[0026] In some specific embodiments, the mass concentration of the borax-alcoholamine polymer obtained by the cross-linking reaction of the alcoholamine compound, borax and water is 60-70wt%, and the mass concentration of the network structure polymer cement grinding aid is 60-70wt%.

[0027] In some specific embodiments, the glycol compound is one or more of tetraethylene glycol, pentaethylene glycol, and hexaethylene glycol.

[0028] In some specific embodiments, the purity of the nano-silicon dioxide is greater than 99.5%, the hydroxyl content is greater than 40%, and the particle size is 10 nm to 30 nm.

[0029] In some specific embodiments, during the cement vertical mill grinding process, the amount of the network structure polymer cement grinding aid is 0.03-0.07wt% of the cement.

[0030] The present invention also provides a method for preparing the above-mentioned network structure polymer cement grinding aid, comprising the following steps: S1. cross-linking an olamine compound, borax and water to obtain a borax-olamine polymer; S2. Add glycol compound, nano silicon dioxide and water to the borax-alcoholamine polymer obtained in step S1 and stir to obtain the network structure polymer cement grinding aid.

[0031] In some specific embodiments, step S1 comprises: S1.1 Mix the alcohol amine compound, borax and water to obtain a mixed solution, stir and heat it to 50-70°C, add alkaline regulating solution while stirring to adjust the pH of the system to 9.0-10, and carry out cross-linking reaction for 40-60 minutes; S1.2 adding an acidic regulating liquid to adjust the pH of the system to 6-7 to terminate the cross-linking reaction, thereby obtaining the borax-alcoholamine polymer.

[0032] In some specific embodiments, the alkaline regulating liquid is one or more of sodium hydroxide, lithium hydroxide and potassium hydroxide solutions, with a concentration range of 0.5~1wt%, and the acidic regulating liquid is one or more of acetic acid, tartaric acid and maleic acid solutions, with a concentration range of 0.1~0.4wt%.

[0033] In some specific embodiments, the stirring time in step S2 is 25 to 40 minutes.

[0034] The following are specific examples, which provide the sources of the test materials. Unless otherwise specified, they can all be obtained through commercial channels. The source of the alcoholamine compound is obtained through commercial sales, and the manufacturers are Wuhan Lanabai Pharmaceutical Chemical Co., Ltd., Hangzhou Tuomu Technology Co., Ltd., Qieke New Material Technology (Shanghai) Co., Ltd., Guangzhou Yuhao Trading Co., Ltd., Shanghai Dibai Biotechnology Co., Ltd., and Shanghai Zhanyun Chemical Co., Ltd. The source of the nano-silicon dioxide is obtained through commercial sales, and the manufacturers are Hubei Huifu Nanomaterial Co., Ltd., Jiangsu Runfeng Synthesis Technology Co., Ltd., Guangdong Wengjiang Chemical Reagent Co., Ltd., Shanghai Naio Nanotechnology Co., Ltd., Shanghai Zhenlishi Network Technology Co., Ltd., and Hangzhou Jiupeng New Materials Co., Ltd.

[0035] Example 1 Add 2 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1 mol borax and water into a container, heat to 50°C while stirring, add sodium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 40 minutes; Acetic acid was added to adjust the pH of the system to 6.0, and stirring was continued for 30 minutes to obtain borax-alcoholamine polymer 1; 1 mol of tetraethylene glycol, 0.5 mol of nano-silicon dioxide and water were added, and stirred for 25 minutes to obtain a network structure polymer cement grinding aid.

[0036] Example 2 4 mol N,N,N',N'-tetra-(2-hydroxypropyl)ethylenediamine, 1 mol borax and water were added to a container and heated to 60°C while stirring. During stirring, lithium hydroxide was added to adjust the pH of the system to 10.0 and the reaction was continued for 60 minutes. Tartaric acid was added to adjust the pH of the system to 7.0, and stirring was continued for 40 min to obtain borax-alcoholamine polymer 2; 1 mol of pentaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 40 minutes to obtain a network structure polymer cement grinding aid.

[0037] Example 3 3 mol N,N,N',N'-tetrakis(2-hydroxyethyl) adipamide, 1 mol borax and water were added into a container and heated to 70°C while stirring. Potassium hydroxide was added during stirring to adjust the pH of the system to 9.0 and the reaction was continued for 40 minutes. Maleic acid was added to adjust the pH of the system to 6.0, and stirring was continued for 35 minutes to obtain borax-alcoholamine polymer 3; 1.5 mol of hexaethylene glycol, 0.6 mol of nano-silicon dioxide and water were added, and stirred for 25 minutes to obtain a network structure polymer cement grinding aid.

[0038] Example 4 Add 1 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 1 mol borax and water into a container, heat to 55°C while stirring, add sodium hydroxide and lithium hydroxide during stirring to adjust the pH of the system to 10.0, and react for 60 minutes; Acetic acid and maleic acid were added to adjust the pH of the system to 7.0, and stirring was continued for 38 minutes to obtain borax-alcoholamine polymer 4; 1 mol of tetraethylene glycol, 1 mol of pentaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 40 minutes to obtain a network structure polymer cement grinding aid.

[0039] Example 5 Add 2 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 2 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, heat to 65°C while stirring, add potassium hydroxide and lithium hydroxide during stirring to adjust the pH of the system to 10.0, and react for 55 minutes; Acetic acid and tartaric acid were added to adjust the pH of the system to 6.0, and stirring was continued for 40 minutes to obtain borax-alcoholamine polymer 5; 1 mol of tetraethylene glycol, 1 mol of hexaethylene glycol, 0.8 mol of nano-silicon dioxide and water were added and stirred for 30 minutes to obtain a network structure polymer cement grinding aid.

[0040] Example 6 Add 2 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 2 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, heat to 68°C while stirring, add potassium hydroxide and sodium hydroxide during stirring to adjust the pH of the system to 10.0, and react for 48 minutes; Maleic acid and tartaric acid were added to adjust the pH of the system to 7.0, and stirring was continued for 30 minutes to obtain borax-alcoholamine polymer 6; 0.5 mol of pentaethylene glycol, 0.5 mol of hexaethylene glycol, 0.9 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0041] Example 7 Add 1.2 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1.3 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 1.5 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, heat to 53°C while stirring, add potassium hydroxide, sodium hydroxide and lithium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 45 minutes; Acetic acid, maleic acid and tartaric acid were added to adjust the pH of the system to 7.0, and stirring was continued for 36 minutes to obtain borax-alcoholamine polymer 7; 0.5 mol of tetraethylene glycol, 0.5 mol of pentaethylene glycol, 0.5 mol of hexaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 32 minutes to obtain a network structure polymer cement grinding aid.

[0042] Example 8 Add 2.5 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1 mol borax and water into a container, heat to 60°C while stirring, add potassium hydroxide, sodium hydroxide and lithium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 60 minutes; Acetic acid, maleic acid and tartaric acid were added to adjust the pH of the system to 7.0, and stirring was continued for 30 minutes to obtain borax-alcoholamine polymer 8; 0.6 mol of tetraethylene glycol, 0.6 mol of pentaethylene glycol, 0.5 mol of nano-silicon dioxide and water were added and stirred for 28 minutes to obtain a network structure polymer cement grinding aid.

[0043] Example 9 Add 3.5 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1 mol borax and water into a container, heat to 57°C while stirring, add sodium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 45 minutes; Acetic acid was added to adjust the pH of the system to 7.0, and stirring was continued for 40 min to obtain borax-alcoholamine polymer 9; 0.7 mol of tetraethylene glycol, 1 mol of hexaethylene glycol, 0.5 mol of nano-silicon dioxide and water were added and stirred for 30 minutes to obtain a network structure polymer cement grinding aid.

[0044] Example 10 3 mol N,N,N',N'-tetra-(2-hydroxypropyl)ethylenediamine, 1 mol borax and water were added into a container, and the temperature was raised to 63°C while stirring. During the stirring, sodium hydroxide and lithium hydroxide were added to adjust the pH of the system to 10.0, and the reaction was continued for 56 minutes. Acetic acid and maleic acid were added to adjust the pH of the system to 7.0, and stirring was continued for 35 minutes to obtain borax-alcoholamine polymer 10; 0.3 mol of pentaethylene glycol, 1 mol of hexaethylene glycol, 0.5 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0045] Embodiment 11 4 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water were added into a container, and the temperature was raised to 60°C while stirring. During the stirring period, potassium hydroxide was added to adjust the pH of the system to 9.0, and the reaction was continued for 45 minutes. Acetic acid was added to adjust the pH of the system to 6.0, and stirring was continued for 35 minutes to obtain borax-alcoholamine polymer 11; 1 mol of pentaethylene glycol, 0.5 mol of hexaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0046] Example 12 Add 1.2 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1.2 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 1.2 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, raise the temperature to 60°C while stirring, add potassium hydroxide, sodium hydroxide and lithium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 60 minutes; Acetic acid, maleic acid and tartaric acid were added to adjust the pH of the system to 7.0, and stirring was continued for 33 minutes to obtain borax-alcoholamine polymer 12; 1 mol of tetraethylene glycol, 1 mol of pentaethylene glycol, 0.6 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0047] Embodiment 13 Add 1.5 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 1.5 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, heat to 60°C while stirring, add potassium hydroxide and sodium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 49 minutes; Acetic acid was added to adjust the pH of the system to 7.0, and stirring was continued for 30 min to obtain borax-alcoholamine polymer 13; 1 mol of tetraethylene glycol, 1 mol of pentaethylene glycol, 0.8 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0048] Embodiment 14 Add 1.4 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1.4 mol N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, 1 mol borax and water into a container, raise the temperature to 60°C while stirring, add potassium hydroxide and sodium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 55 minutes; Acetic acid was added to adjust the pH of the system to 7.0, and stirring was continued for 30 min to obtain borax-alcoholamine polymer 14; 0.4 mol of tetraethylene glycol, 0.4 mol of pentaethylene glycol, 0.4 mol of hexaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0049] Embodiment 15 Add 1.5 mol N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, 1.5 mol N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide, 1 mol borax and water into a container, heat to 60°C while stirring, add potassium hydroxide and sodium hydroxide during stirring to adjust the pH of the system to 9.0, and react for 53 minutes; Acetic acid and maleic acid were added to adjust the pH of the system to 7.0, and stirring was continued for 30 minutes to obtain borax-alcoholamine polymer 15; 0.5 mol of tetraethylene glycol, 0.5 mol of pentaethylene glycol, 0.5 mol of hexaethylene glycol, 1 mol of nano-silicon dioxide and water were added and stirred for 35 minutes to obtain a network structure polymer cement grinding aid.

[0050] Comparative Example 1 Example 9 was repeated, except that an equal amount of the nano-silicon dioxide was replaced by water and other conditions remained unchanged, to obtain a mixture 1.

[0051] Comparative Example 2 Example 10 was repeated, except that an equal amount of the ethanolamine compound was replaced by water and other conditions remained unchanged, to obtain a mixture 2.

[0052] Comparative Example 3 Example 14 was repeated, except that an equal amount of the glycol compound was replaced by water while keeping other conditions unchanged, to obtain a mixture 3.

[0053] Comparative Example 4 Example 15 was repeated, except that an equal amount of borax was replaced by water while keeping other conditions unchanged, to obtain mixture 4.

[0054] Comparative Example 5 Example 14 was repeated, except that equal amounts of borax, amine compounds, glycol compounds, and nano-silicon dioxide were replaced by triethanolamine, and other conditions remained unchanged, to obtain mixture 5.

[0055] Comparative Example 6 Example 15 was repeated, except that equal amounts of borax, glycol compound, amine compound and nano-silica were replaced by diethyl monoisopropanolamine, and other conditions remained unchanged, to obtain mixture 6.

[0056] The network structure polymer cement grinding aids prepared in the above Examples 1-15, the mixtures prepared in Comparative Examples 1-6, and a commercially available vertical mill grinding aid were tested and evaluated.

[0057] The viscosity of the borax-alcoholamine polymers 1 to 15 in Examples 1 to 15 of the present invention was tested. The results are shown in Table 1.

[0058] Table 1 Viscosity test

[0059] It can be seen from Table 1 that the borax-alcoholamine polymer is within the design range during the preparation of the network polymer cement grinding aid for vertical mill, indicating that the preparation process is carried out according to the design and the designed network structure polymer cement grinding aid can be finally obtained.

[0060] The reticulated polymer cement grinding aid for vertical mill prepared in Example 1-15 was subjected to grinding test in a φ5370 mm vertical mill. The cement ratio was: 80% clinker, 15% slag, and 5% gypsum. The cement grinding aid was added to the cement raw materials before grinding. The specific surface area of ​​the cement was controlled to be 335±10 m 2 / Kg, the cement performance evaluation test was carried out on the samples produced and discharged from the vertical mill, and the results are shown in Table 2. Among them, further comparative evaluation was carried out with borax, glycol compounds, amine compounds, nano-silica, a commercially available vertical mill cement grinding aid and a blank without cement grinding aid, and the dosage of different cement grinding aids was 0.05% (percentage of the total mass of cement raw materials).

[0061] Table 2 Production and cement performance evaluation

[0062] As can be seen from Table 2, the network structure polymer cement grinding aid of the present invention can significantly improve the strength of cement while improving the grinding efficiency compared with the blank group. In addition, compared with Comparative Examples 1-6, the network structure polymer cement grinding aid prepared by the present invention has higher yield and strength.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A network structure polymer cement grinding aid, characterized in that: It is composed of borax-alcoholamine polymer, glycol compound, nano-silica and water; The borax-alcoholamine polymer is obtained by cross-linking an alcoholamine compound, borax and water under alkaline conditions, and has a viscosity of 1500-2000 mPa·S; The molar ratio of the alcohol amine compound, borax, glycol compound and nano silicon dioxide is (2-4):1:(1-2):(0.5-1).

2. The network structure polymer cement grinding aid according to claim 1, characterized in that: The alcohol amine compound is one or more of N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine, N,N,N',N'-tetrakis-(2-hydroxypropyl)ethylenediamine, and N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide.

3. The network structure polymer cement grinding aid according to claim 1, characterized in that: The mass concentration of the borax-alcoholamine polymer obtained by cross-linking the olamine compound, borax and water is 60-70wt%, and the mass concentration of the network structure polymer cement grinding aid is 60-70wt%.

4. The network structure polymer cement grinding aid according to claim 1, characterized in that: The glycol compound is one or more of tetraethylene glycol, pentaethylene glycol and hexaethylene glycol.

5. The network structure polymer cement grinding aid according to claim 1, characterized in that: The purity of the nano silicon dioxide is greater than 99.5%, the hydroxyl content is greater than 40%, and the particle size is 10nm-30nm.

6. The network structure polymer cement grinding aid according to any one of claims 1 to 5, characterized in that: In the cement vertical mill grinding process, the dosage of the network structure polymer cement grinding aid is 0.03-0.07wt% of the cement.

7. The method for preparing a network structure polymer cement grinding aid according to any one of claims 1 to 6, characterized in that: The steps include: S1. cross-linking an olamine compound, borax and water to obtain a borax-olamine polymer; S2. Add glycol compound, nano silicon dioxide and water to the borax-alcoholamine polymer obtained in step S1, and stir to obtain the network structure polymer cement grinding aid.

8. The preparation method according to claim 7, characterized in that: Step S1 includes: S1.1 Mix the alcohol amine compound, borax and water to obtain a mixed solution, stir and heat it to 50-70°C, add alkaline regulating solution while stirring to adjust the pH of the system to 9.0-10, and carry out cross-linking reaction for 40-60 minutes; S1.2 adding an acidic regulating liquid to adjust the pH of the system to 6-7 to terminate the cross-linking reaction, thereby obtaining the borax-alcoholamine polymer.

9. The preparation method according to claim 8, characterized in that: The alkaline regulating liquid is one or more of sodium hydroxide, lithium hydroxide and potassium hydroxide solutions, and the concentration range is 0.5-1wt%. The acidic regulating liquid is one or more of acetic acid, tartaric acid and maleic acid solutions, and the concentration range is 0.1-0.4wt%.

10. The preparation method according to claim 7, characterized in that: The stirring time in step S2 is 25 to 40 minutes.